Genetic Diversity and Characteristics of blaNDM-Positive Plasmids in Escherichia coli - Zhang, Zhiren; Guo, Hengzhao; Li, Xiaodong; Li, Wenting; Yang, Guang; Ni, Wenjun; Zhan, Meixiao; Lu, Ligong; Zhang, Zhenlin; Li, Xiaobin; Zhou, Zhiling (Frontiers in Microbiology, 2021)
New Delhi metallo-β-lactamases (NDMs), including at least 28 variants, are a rapidly emerging family of β-lactamases worldwide, with a variety of infections caused by NDM-positive strains usually associated with very poor prognosis and high mortality. NDMs are the most prevalent carbapenemases in Escherichia coli (E. coli) worldwide, especially in China. The vast majority of blaNDM cases occur on plasmids, which play a vital role in the dissemination of blaNDM. To systematically explore the relationships between plasmids and blaNDM genes in E. coli and obtain an overall picture of the conjugative and mobilizable blaNDM-positive plasmids, we analyzed the variants of blaNDM, replicon types, phylogenetic patterns, conjugative transfer modules, host STs, and geographical distributions of 114 blaNDM-positive plasmids, which were selected from 3786 plasmids from 1346 complete whole genomes of E. coli from the GenBank database. We also established links among the characteristics of blaNDM-positive plasmids in E. coli. Eight variants of blaNDM were found among the 114 blaNDM-positive plasmids, with blaNDM–5 (74 blaNDM–5 genes in 73 plasmids), and blaNDM–1 (31 blaNDM–1 genes in 28 plasmids) being the most dominant. The variant blaNDM–5 was mainly carried by the IncX3 plasmids and IncF plasmids in E. coli, the former were mainly geographically distributed in East Asia (especially in China) and the United States, and the latter were widely distributed worldwide. IncC plasmids were observed to be the predominant carriers of blaNDM–1 genes in E. coli, which were mainly geographically distributed in the United States and China. Other blaNDM–1-carrying plasmids also included IncM2, IncN2, and IncHI1. Moreover, the overall picture of the conjugative and mobilizable blaNDM-positive plasmids in E. coli was described in our study. Our findings enhance our understanding of the genetic diversity and characteristics of blaNDM-positive plasmids in in E. coli.